Purchase Decisions: Brand Image and Product Quality - Andi Hidayat; Marhaeni Sabil; Muhammad Nurhadi N; Sofyan Hamid Indar (YUME : Journal of Management, 2020)
The purpose of this study was to determine the effect of brand image and product quality on purchasing decisions Donut J-Co, both partially and simultaneously. Where in this study using a sample of a total population of 97 respondents with solving sampling techniques and the use of multiple regression analysis tools with SPSS software 23.The results showed that brand image partially had a positive and significant effect on the purchase decision of Donut J-Co, product quality showed the results that had a positive and significant effect on the purchase decision of Donut J-Co, while for simultaneous testing the results showed that brand image and product quality affected positive and significant towards J-Co's buying decision. Keywords: Purchase Decision, Brand Image, Product Quality